2018
DOI: 10.21273/horttech03979-18
|View full text |Cite
|
Sign up to set email alerts
|

Curricula Influence College Student Knowledge and Attitudes Regarding Invasive Species

Abstract: Negative impacts from invasive species present a global problem. Consequently, invasive species biology has emerged as an important subdiscipline of conservation biology. One of the goals of invasive species biology is to educate the public about impacts and potential control of invasive species. The purpose of this study was to determine if a lecture, a lecture and laboratory learning model, or both influence college student learning gains and whether increase in knowledge results in changes in attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…In this sense, Waliczek et al [25] indicated the need to include this topic in educational curricula, with the aim of improving students' training. The same authors considered that this topic should pay special attention to IAS impacts and their control [59]. The present results, together with previous evidence (e.g., [39]), highlight the relevance of an appropriate education, either formal or informal, about IAS.…”
Section: Discussionsupporting
confidence: 78%
“…In this sense, Waliczek et al [25] indicated the need to include this topic in educational curricula, with the aim of improving students' training. The same authors considered that this topic should pay special attention to IAS impacts and their control [59]. The present results, together with previous evidence (e.g., [39]), highlight the relevance of an appropriate education, either formal or informal, about IAS.…”
Section: Discussionsupporting
confidence: 78%
“…The IAS instruction appears to be more effective in higher education than in high school since most students claimed to have learned about invasive species during undergraduate courses. Thus, we found that higher education can positively influence academics' knowledge and attitudes concerning IAS (Waliczek et al 2018). Although university students have more access to learning about the topic, this knowledge seems insufficient since most students do not consider themselves well informed about the subject, indicating shortcomings and flaws in the students' knowledge about IAS.…”
Section: Discussionmentioning
confidence: 77%
“…The use of alternative techniques and methodologies, such as lectures, practical classes, and case studies, can effectively improve teaching and learning and, consequently, reverse these deficiencies. Fox and Loope (2007) and Waliczek et al (2018) investigated the use of simple pedagogical techniques and methodologies, such as case studies, and found a significant increase in knowledge about invasive species, mainly by contextualizing the theme with the students' daily lives. In this way, developing well-planned curricular activities and targeting specific audiences allow better education results on IAS (Vanderhoeven et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Crooks and Soule (1996) noted that many estimates of the time between initial introduction and population explosion are likely conservative due to an additional lag effect, which is our ability to detect the presence of a new invasive species. While there is a need to increase public awareness and knowledge of the presence and impact of invasive plants in general (Daab and Flint, 2010;Oxley et al, 2016;Waliczek et al, 2018), one aspect of invasive plant detection is distinguishing harmful invasive plants from native plants when they look alike. Instances may also arise where a newly emerging invasive plant is similar in appearance to an already naturalized invasive, which also may delay detection and response before the new invader becomes more widespread and or problematic.…”
mentioning
confidence: 99%